Genotype by environment interaction and grain yield stability of drought tolerant cowpea landraces in Ethiopia - Mekonnen, T.W.; Mekbib, Firew; Amsalu, B.; Gedil, Melaku A; Labuschagne, Maryke T. (Springer, 2022)
Cowpea is one of the most important indigenous food and forage legumes in Africa. It serves as a primary source of protein for poor farmers in drought-prone areas of Ethiopia. The crop is used as a source of food, and insurance crop during the dry season. Cowpea is adaptable to a wide range of climatic conditions. Despite this, the yield of the crop is generally low due to lack of stable and drought-tolerant varieties. In this study, 25 cowpea genotypes were evaluated in five environments using a lattice design during the 2017 and 2018 main cropping seasons. The objectives of this study were to estimate the magnitude of genotype by environment interaction (GEI) and grain yield stability of selected drought-tolerant cowpea genotypes across different environments. The additive main effect and multiplicative interaction (AMMI) model indicated the contribution of environment, genotype and GEI as 63.98, 2.66% and 16.30% of the total variation for grain yield, respectively. The IPCA1, IPCA2 and IPCA3 were all significant and explained 45.47%, 28.05% and 16.59% of the GEI variation, respectively. The results from AMMI, cultivar superior measure, genotype plus genotype-by-environment biplot yield stability index, and AMMI stability value analyses identified NLLP-CPC-07-145-21, NLLP-CPC-103-B and NLLP_CPC-07-54 as stable and high yielding genotypes across environments. Thus, these genotypes should be recommended for release for production in drought-prone areas. NLLP-CPC-07-143, Kanketi and CP-EXTERETIS were the least stable. The AMMI1 biplot showed that Jinka was a high potential and favorable environment while Babile was an unfavorable environment for cowpea production.